Law of banking - Chorley, Robert Samuel Theodore Chorley; Holden, James Milnes (London : Sweet & Maxwell, 1974)
In eight years no less than twenty-five Acts have been passed through Parliament. Some of these Acts discussed in this book are the Race Relations Act 1968, and Banking and Financial Dealings Act 1970. The author further made brief references to the Local Government Act 1972 and the European Communities Act 1972.
Includes bibliographical references and index.
ne 09/08/2019
Loans
Keywords: Banking law